A deep learning/machine learning approach for anomaly based network intrusion detection - Almuhanna, Reem; Dardouri, Samia (Frontiers in Artificial Intelligence, 2025)
IntroductionThe increasing complexity and frequency of cybersecurity threats necessitate the development of advanced detection systems capable of identifying both known and emerging attacks. In this study, we present a hybrid anomaly-based Network Intrusion Detection System (NIDS) that integrates multiple machine learning and deep learning algorithms, including XGBoost, Random Forest, Graph Neural Networks (GNN), Long Short-Term Memory (LSTM) networks, and Autoencoders.MethodsThe proposed system was trained on a large-scale dataset comprising over 5.6 million network traffic records. Comprehensive data preprocessing and feature engineering were applied, and the Synthetic Minority Over-sampling Technique (SMOTE) was employed to address class imbalance. To enhance robustness and generalization, a weighted soft-voting ensemble strategy was used to combine predictions from the individual models.ResultsThe experimental evaluation demonstrated near-perfect performance, with accuracy, precision, recall, and F1-score values approaching 100% on the primary dataset. These results were validated through rigorous 5-fold cross-validation.DiscussionEvaluation on an independent benchmark dataset confirmed the strong generalizability and robustness of the proposed model across diverse intrusion scenarios. These findings highlight the effectiveness of the hybrid ensemble framework in significantly improving intrusion detection capabilities within complex and dynamic network environments.